The analysis of phraseological synonymic euphemisms with the meaning “to die” - Hilola Inomovna Ismailova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The current article is devoted to the study of one synonymic group of phraseological euphemisms which is investigated from the point of view of different types of synonyms and the synonymic group of phraseological euphemisms with the meaning “to die” and have been analyzed. The analysis of phraseological synonymic euphemisms with the meaning “to die” has shown that the synonymic group consists of different groups of synonyms: equivalent, stylistic and stylistic-ideographic.